OPTIMIZATION OF PRICING AND COST PLANNING USING LINEAR FUNCTIONS: AN ECONOMIC MATHEMATICS PERSPECTIVE ON FINANCIAL STRATEGY AT CAKE MY DAY - Hery saputra; Nina Zakiah; Nurina Happy (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Pricing and cost planning are critical aspects of business management, especially for small enterprises like the "Cakemyday" cake shop. Proper financial planning ensures sustainability and profitability in a competitive market. This study aims to analyze the financial feasibility of "Cakemyday" by calculating the Break-Even Point (BEP) and determining the optimal selling price based on cost structures and demand functions.A quantitative approach was employed, utilizing financial data, including fixed costs, variable costs, and demand function analysis. The BEP calculation determined the minimum number of units required to cover all expenses, while the demand function was derived from historical pricing and sales data to understand consumer behavior.The findings indicate that "Cakemyday" needs to sell 78 units to reach BEP, with a contribution margin of Rp 90,000 per unit. Furthermore, to achieve a profit target of Rp 3,000,000, an optimal selling price of approximately Rp 188,000 per unit was determined. The demand function analysis revealed a negative correlation between price and quantity demanded, supporting strategic pricing decisions.The study concludes that understanding financial metrics and consumer behavior is essential for sustainable business growth. It is recommended that "Cakemyday" implement targeted marketing strategies and monitor pricing dynamics to enhance profitability. Future research may explore external factors affecting demand and conduct comparative studies with similar businesses.